Sweetpotato silage: Nutritious and a ordable all year-round feed for pig farmers - International Potato Center (2017)
In Uganda, researchers have finalized the supplementation strategy and the cost-benefit analysis for sweetpotato silage for pig production. This is expected to contribute to the transformation of the livestock industry whose major production constraint is expensive and poor quality feeds.